The impact of credit risk on market discipline: Exploring the moderating role of corporate governance through Generalized Method of Moments (GMM) analysis in banking companies - Juliana, Ahmad; Najmuddin, Najmuddin; Junaid, Muhammad Tharmizi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
High credit risk poses a significant threat to banks, underscoring the necessity to examine the effectiveness of good corporate governance in mitigating such risks. This study aims to assess the impact of credit risk, represented by non-performing loans (NPLs), on market discipline, reflected through deposit growth, and the moderating role of good corporate governance, focusing on board size and institutional ownership, in this dynamic. Data for the study were sourced from the financial reports of banking companies on their official websites, IDN Financial, and the Indonesia Stock Exchange. The study used a purposive sampling method to analyze a sample comprising 30 banking companies and yielded 300 observations. The research methodology involved dynamic panel regression analysis using the Generalized Method of Moments (GMM) technique. The findings reveal that non-performing loans negatively impact deposit growth. However, it was also found that board size and institutional ownership could positively moderate the adverse effects of non-performing loans on deposit growth. This suggests that market discipline, manifesting as a reduction in deposits and an escalation in credit risk within the Indonesian banking sector, can be effectively managed and mitigated through the strategic implementation of good corporate governance practices, particularly by optimizing board size and enhancing institutional ownership. These mechanisms enable more robust market discipline, contributing to better credit risk management and promoting healthier deposit growth.